Análisis de los modelos de economía circular para el aprovechamiento de residuos plásticos PET en Bogotá (2023)
Due to the global problem on the amount of solid waste found in the environment, which profoundly affects the ecosystems and the quality of life of those who are around, an analysis was carried out whose purpose is to find ideal activities which are under a circular economy and reverse logistics strategy, mainly for the plastics industry in Bogotá.